ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA PASCAPANDEMI COVID-19 - Ramadani, Akhmad Asrul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The impact of easing and lifting the policy of limiting community activities in dealing with the Covid-19 pandemic in Indonesia is starting to be felt. Go-jek as an online transportation service provider in Indonesia, especially Malang City, is experiencing recovery and contributing quite a lot to GRDP. However, of all Go-jek partners, Go-ride driver partners have the lowest productivity compared to other partners. The purpose of this research is to find out the factors that influence the labor productivity of post-pandemic Go-ride driver partners in Malang City. The method used in this study is multiple linear regression analysis with classical assumptions and hypothesis testing. The data used are age, wages, work experience, and education level of Go-ride driver partners after the Covid-19 pandemic in Malang City. The data was obtained from direct interviews with Go-ride driver partners in Malang City. The results showed that age, wages, work experience, and education level had a positive and significant effect on the productivity of post-Covid-19 Go-ride driver partners in Malang City. Wages are the variable that has the most dominant influence compared to other independent variables.